2022
DOI: 10.1101/2022.09.12.507592
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meggie – easy-to-use graphical user interface for M/EEG analysis based on MNE-python

Abstract: In the last decades, electrophysiological imaging methodology has seen many advances and the computational power in the neuroscience laboratories has steadily increased. Still, the new methodologies are unavailable for many. There is a need for more versatile analysis approaches for neuroscience specialists without a programming background. Using a software which provides standard pipelines, provides good default values for parameters, has a good multi-subject support, and stores the used analysis steps with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…MEG data was downsampled resulting in a sampling rate of 500 Hz. Thereafter MEG data was exported to Meggie, an MNE-python-based graphical user interface (Heinilä and Parviainen, 2022), where independent component analysis (ICA) was used to extract, visually inspect, and manually remove common artifacts of cardiac and ocular origin. Since gradiometers are optimal for recording data from superficial sources and they have a narrow spatial sensitivity pattern, the subsequent analyses were conducted using only planar gradiometers.…”
Section: Methodsmentioning
confidence: 99%
“…MEG data was downsampled resulting in a sampling rate of 500 Hz. Thereafter MEG data was exported to Meggie, an MNE-python-based graphical user interface (Heinilä and Parviainen, 2022), where independent component analysis (ICA) was used to extract, visually inspect, and manually remove common artifacts of cardiac and ocular origin. Since gradiometers are optimal for recording data from superficial sources and they have a narrow spatial sensitivity pattern, the subsequent analyses were conducted using only planar gradiometers.…”
Section: Methodsmentioning
confidence: 99%
“…An in-house EEG data processing pipeline, EEG-pyline, was used for signal preprocessing and spectral analysis efforts ( Anijärv, 2022 ). The specific code (i.e., Jupyter notebook) used for this study can be found in the ‘studies’ folder within the GitHub repository.…”
Section: Methodsmentioning
confidence: 99%
“…Possible head movements occurring during the measurement with respect to the initial head position were also corrected using Maxfilter™ 2.2 software. The rest of the pre-processing was performed with Meggie (CIBR, Jyväskylä, Finland; Heinilä & Parviainen, 2022), a graphical user interface for MNE-Python (Gramfort et al, 2014). With the use of this software, epochs contaminated with eye movements (as measured with EOG) or cardiac artifacts (measured by an MEG channel) were removed from the analysis.…”
Section: Methodsmentioning
confidence: 99%